Disrupted Circadian Rhythms as a Novel Driver of Sarcopenia: Mechanisms, Evidence, and Future Directions - Alina Deniza Ciubean; Theodor Popa; Viorela Mihaela Ciortea; Gabriela Dogaru; Laszlo Irsay (Balneo and PRM Research Journal, 2025)
Sarcopenia, a progressive and generalized skeletal muscle disorder characterized by loss of muscle mass, strength, and function, represents a major public health concern in aging populations. It contributes significantly to frailty, reduced mobility, falls, and mortality among older adults. While multifactorial in origin, emerging research suggests a compelling link between circadian rhythm disruption and the pathogenesis of sarcopenia. Circadian rhythms, governed by the central pacemaker in the suprachiasmatic nucleus (SCN) and regulated by a transcription-translation feedback loop involving core clock genes (BMAL1, CLOCK, PER, and CRY), orchestrate diverse physiological processes including metabolism, inflammation, hormone release, and mitochondrial function. Skeletal muscle harbors its own peripheral clock, which plays a critical role in regulating protein synthesis, glucose utilization, and mitochondrial dynamics. Recent evidence indicates that age-related alterations in circadian rhythms, as well as external circadian disruptions due to shift work, light exposure, or irregular sleep-wake cycles, may contribute to sarcopenia through hormonal dysregulation, chronic inflammation, impaired mitochondrial biogenesis, and reduced autophagy. Animal models with muscle-specific clock gene deletions exhibit muscle atrophy, increased oxidative stress, and reduced regenerative capacity. Epidemiological studies further support a relationship between circadian misalignment and decreased muscle strength and mass in humans. Additionally, interventions such as time-restricted feeding, scheduled exercise, and light therapy show promise in restoring circadian alignment and potentially mitigating muscle loss. This review aims to provide a comprehensive overview of current knowledge on the circadian regulation of skeletal muscle and the implications of circadian disruption for sarcopenia. We explore molecular mechanisms, epidemiological data, experimental studies, and emerging therapeutic strategies. Understanding the interplay between the circadian clock and muscle health may reveal novel approaches for preventing and managing sarcopenia in the aging population.